PENGARUH KUALITAS SISTEM INFORMASI, KUALITAS INFORMASI, KEPUASAN PENGGUNA, DAN KOMPETENSI SUMBER DAYA MANUSIA TERHADAP PENGGUNAAN SISTEM ERP (ENTERPRISE RESOURCE PLANNING) BERBASIS TAM (TECHNOLOGY ACCEPTANCE MODEL) - Akram Akram; Animah Animah; Prayitno Basuki (Master of Management, Mataram University, 2017)
The objective of this research are to determine influance of system information quality, informtion quality and using of competence basis technology acceptance model enterprice resorces planning on PT. Telkom Kandatel Mataram.This research using multiple linear regressions with SPSS program. The result showed that information system quality and information quality has no influence on the implementation of Technology Acceptance Model –Based ERP system. Meanwhile, user’s satisfaction and human resource competency has influence on the Technology Acceptance Model–Based ERP system.Keywords : Information System Quality, Information Quality, User’s Satisfaction, Human Resource Competency, Enterprise Resource Planning (ERP), TAM-Based (Technology Acceptance Model)